2017
DOI: 10.1126/scitranslmed.aam5434
|View full text |Cite
|
Sign up to set email alerts
|

VP4- and VP7-specific antibodies mediate heterotypic immunity to rotavirus in humans

Abstract: Human rotaviruses (RVs) are the leading cause of severe diarrhea in young children worldwide. The molecular mechanisms underlying the rapid induction of heterotypic protective immunity to RV, which provides the basis for the efficacy of licensed monovalent RV vaccines, have remained unknown for more than 30 years. We used RV-specific single cell-sorted intestinal B cells from human adults, barcode-based deep sequencing of antibody repertoires, monoclonal antibody expression, and serologic and functional charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 48 publications
4
109
0
1
Order By: Relevance
“…Thus, safer replication-incompetent rotavirus vaccines are required. One study identified memory B cells in the submucosa of adult intestinal tissue that produced broadly cross-reactive and cross-neutralizing antibodies specific to VP5*; accordingly, recombinant VP5* might represent a broadly efficient candidate for a rotavirus vaccine 191 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, safer replication-incompetent rotavirus vaccines are required. One study identified memory B cells in the submucosa of adult intestinal tissue that produced broadly cross-reactive and cross-neutralizing antibodies specific to VP5*; accordingly, recombinant VP5* might represent a broadly efficient candidate for a rotavirus vaccine 191 .…”
Section: Discussionmentioning
confidence: 99%
“…However, many neutralizing antigen epitope differences were identified on the VP4 protein between the Chinese PoRV strains and the RCE strains, suggesting the reduced effectiveness of the RCE strains. Rotavirus antigens and serotypes are diverse, suggesting that obtaining extensive protective immunity requires immunization or infection with multiple antigens (Nair et al., ). More information is needed to understand the diversity of field strains and to develop an effective polyvalent vaccine as a possible means of PoRV control in China.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential disadvantages of inactivated vaccines become apparent when the antigen or antigens required to induce protective immunity are difficult to synthesize artificially or when immunity is most potent when it is directed at multiple antigens that are correctly folded only on the actual or recombinant multiprotein viral particle. Of note, RVs have at least two separate proteins (VP4 and VP7) that are targets of protective antibodies, and VP4 is cleaved by enteric trypsin into two separate protein components: VP8* and VP5* [78]. Both VP8* and VP5* are individually targeted by protective antibody responses.…”
Section: Taking Advantage Of Rotavirus Host Range Restriction To Rmentioning
confidence: 99%